2018
DOI: 10.1136/svn-2018-000142
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke mRNA expression profile of MMPs: effect of genetic deletion of MMP-12

Abstract: Background and purposeRecent reports from our laboratory demonstrated the post-ischaemic expression profile of various matrix metalloproteinases (MMPs) in rats and the detrimental role of MMP-12 in post-stroke brain damage. We hypothesise that the post-stroke dysregulation of MMPs is similar across species and that genetic deletion of MMP-12 would not affect the post-stroke expression of other MMPs. We tested our hypothesis by determining the pre-ischaemic and post-ischaemic expression profile of MMPs in wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The literature reveals that higher MMP-12 levels have been associated with worse neurological outcome [ 25 ]. MMP-12 upregulation has also been associated with brain ischemia in animal models, with post-ischemic induction higher for MMP-12 than for any other MMPs [ 40 , 41 ]. Other studies have demonstrated that MMP-12 induces brain injury by damaging the BBB after focal cerebral ischemia, while MMP-12 knockdown attenuates this effect [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reveals that higher MMP-12 levels have been associated with worse neurological outcome [ 25 ]. MMP-12 upregulation has also been associated with brain ischemia in animal models, with post-ischemic induction higher for MMP-12 than for any other MMPs [ 40 , 41 ]. Other studies have demonstrated that MMP-12 induces brain injury by damaging the BBB after focal cerebral ischemia, while MMP-12 knockdown attenuates this effect [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of ischemic stroke can induce the activation of stress signals, hypoxia, oxygen–glucose deprivation, and oxidative/nitrosative stress, leading to further neuro-inflammation and fibrosis in the brains [ 8 ]. As the stroke clot is removed, the reperfusion injury may refer to the reactive oxygen species (ROS)/reactive nitrogen species (RNS) response; protein expression of EMC; and its associated proteins such as matrix metalloproteinases [ 42 , 43 ], basement membrane changes [ 44 ], and inflammation induction [ 45 ]. Sun et al [ 17 ] have indicated that ICT pretreatment effectively prevents the neuroinflammatory response and oxidative damage in the brains of cerebral ischemia–reperfusion mice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MMPs have also been implicated in ischemic stroke, with certain MMP gene polymorphisms conferring heightened vulnerability to cerebral ischemia [101,102]. The expression of MMPs appears to be upregulated following episodes of cerebral ischemia [103,104]. Although the relationship between stroke and MMP expression has been well studied, additional studies are needed to determine whether MMP levels following cerebral ischemia correlate with the magnitude of poststroke muscle atrophy.…”
Section: Mmpsmentioning
confidence: 99%